Propionibacteria as promising tools for the production of pro-bioactive scotta: a proof-of-concept study - Coronas, Roberta; Zara, Giacomo; Gallo, Antonio; Rocchetti, Gabriele; Lapris, Marco; Petretto, Giacomo Luigi; Zara, Severino; Fancello, Francesco; Mannazzu, Ilaria (Frontiers in Microbiology, 2023)
Dairy propionibacteria are Gram positive Actinobacteria, routinely utilized as starters in Swiss type cheese making and highly appreciated for their probiotic properties and health promoting effects. In this work, within the frame of a circular economy approach, 47 Propionibacterium and Acidipropionibacterium spp. were isolated from goat cheese and milk, and ewe rumen liquor, and characterized in view of their possible utilization for the production of novel pro-bioactive food and feed on scotta, a lactose rich substrate and one of the main by-products of the dairy industry. The evaluation of the Minimum Inhibitory Concentration (MIC) of 13 among the most common antibiotics in clinical practice revealed a general susceptibility to ampicillin gentamycin, streptomycin, vancomycin, chloramphenicol, and clindamycin while confirming a lower susceptibility to aminoglycosides and ciprofloxacin. Twenty-five isolates, that proved capable of lactose utilization as the sole carbon source, were then characterized for functional and biotechnological properties. Four of them, ascribed to Propionibacterium freudenreichii species, and harboring resistance to bile salts (growth at 0.7- 1.56 mM of unconjugated bile salts), acid stress (>80% survival after 1 h at pH 2), osmostress (growth at up to 6.5% NaCl) and lyophilization (survival rate > 80%), were selected and inoculated in scotta. On this substrate, the four isolates reached cell densities ranging from 8.11±0.14 to 9.45±0.06 Log CFU mL-1 and proved capable of producing different vitamin B9 vitamers after 72 h incubation at 30°C. In addition, the semi-quantitative analysis following the metabolomics profiling revealed a total production of cobalamin derivatives (vitamin B12) in the range 0.49-1.31 mg L-1, thus suggesting a full activity of the corresponding biosynthetic pathways, likely involving a complex interplay between folate cycle and methylation cycle required in vitamin B12 biosynthesis. These isolates appear interesting candidates for further ad-hoc investigation regarding the production of pro-bioactive scotta.